Humanitarian Intervention versus United Nations Charter: A Critical Appraisal - Hazhar Jabar Qadir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Humanitarian intervention is a widespread and proactive notion. The concept of humanitarian intervention is vast, and the main reason of humanitarian intervention practice connects to help the vulnerable people. This paper looks at the UN Charter to examine the humanitarian intervention on the base of UN Charter. It is undeniable that Charter provides the sovereignty of every member inside UN and gives no legitimate power to any member for using force. Although humanitarian intervention not independently regulated and based on United Nations Charter, it is become internationally an acceptable practice. This paper argue that UN Charter exhibit dual tendency in term of Humanitarian intervention.